Design and implementation of a DC-DC converter - Teo, Wei Shun. (2009)
The modern electronics system consists of different electronics circuit boards running at different DC voltage levels. Most often, a DC-to-DC converter is required to convert the DC supply voltage to the desired operating voltage for these boards. Hence, switching power supplies are preferred over the linear power supplies due to their superior efficiency and performance in their operation. However, the main drawback of the switching converter is the creation of switching noises. These switching noises will become a potential source of electromagnetic interference (EMI) that is capable to cause interference/malfunctions to the surrounding devices. Therefore, the design of the switching DC-DC converter should incorporate ways to reduce the effect of EMI source.